Pengaruh Kombinasi Komposisi Media Tanam Tanah, Arang Sekam, Dan Pupuk Kandang Kotoran Sapi Terhadap Pertumbuhan Dan Hasil Tanaman Sawi (Brassica juncea L.) - Ndiwa, Antonius S.S; Oematan, Shirly S.; Airthur, Moresi M.; Damawi, Ahmad S, (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This research was carried out from February to April 2022, in the yard of Naikoten Satu Output, Kupang City, with the aim of knowing the combination of the composition of soil planting media, husk charcoal, and cow dung on the growth and yield of mustard plants. This research was designed with a completely randomized design (CRD). The treatment being tested was kobasi the composition of soil planting media material, husk charcoal, and cow dung manure which consisted of 6 treatments. P0 = Soil (100%), P1 = Soil with rice husk charcoal (2:1), P2 = Soil with cow manure (2:1), P3 = Soil with rice husk charcoal (1:1), P4 = Soil with cow dung manure (1:1), P5 = Soil with husk charcoal and cow dung manure (1:1:1). Each treatment was carried out in four (4) replications. Observational variable data (height, number of mustard leaves, total plant fresh weight and net fresh weight of mustard greens were analyzed using Variety Print Analysis, followed by Duncan Multiple Range Test (DMRT) at 5% level. The results showed: 1). The combination treatment of soil media composition, husk charcoal, and cow manure had a significant and very significant effect on the height and number of leaves of mustard plants at observations 3 and 4 MSPT (1 WAP and 2 WAP), gross fresh weight, and net fresh weight, 2) . The combination treatment of soil media composition, husk charcoal, and cow manure ratio 1: 1: 1 (P5) gave the best results on plant height, number of leaves, fresh gross weight, fresh net weight, each of which was 28.70 cm for height. plants, 10.50 leaves for the number of leaves, 39.00 grams for fresh gross weight and 35.08 grams for fresh net weight of mustard greens.